Sejarah Prostitusi di Kota Makassar Pascakolonial 1945-1980 - Fajar Sidiq Limola (Yayasan Literasi Sains Indonesia, 2025)
This article explores the dynamics of prostitution in post-independence Makassar (1945–1980) within the context of urban spatial formation, public morality, and state control over sexuality. The research aims to understand how the relocation of prostitution from the Jembatan Besi area to Jalan Nusantara, as well as the emergence of massage parlors as new forms of commercial sex, became part of a broader spatial and social governance strategy by the postcolonial state. Using a social history approach, the study combines archival research, analysis of local media, and oral history interviews. Field data reveals that government policies toward prostitution were ambivalent, formally regulated yet informally tolerated, as long as they did not disrupt public order. Moreover, prostitution functioned as an economic survival strategy for lower-class women, driven by structural inequality and limited access to formal employment. The study finds that female sexuality was symbolically and morally regulated to serve the narrative of urban development. In conclusion, prostitution in post-independence Makassar was not merely a deviant social practice but a reflection of power relations between the state, society, and women’s bodies within the urbanization process.